Loco-regional staging of malignant pleural mesothelioma by integrated 18F-FDG PET/MRI. Issue 115 (June 2019) - Murphy, D.J.; Mak, S.M.; Mallia, A.; Jeljeli, S.; Stirling, J.J.; Goh, V.; Bille, A.; Cook, G.J.R.
Abstract: Aim: To examine the performance of 18 F-FDG PET/MRI in the loco-regional staging of malignant pleural mesothelioma (MPM). Methods: Consecutive subjects with MPM undergoing pre-operative staging with 18 F-FDG PET/CT who underwent a same day integrated 18 F-FDG PET/MRI were prospectively studied. Clinical TNM staging (AJCC 7 th edition) was performed separately and in consensus by two readers on the 18 F-FDG PET/MRI studies, and compared with staging by 18 F-FDG PET/CT, and with final pathological stage, determined by a combination of intra-operative and histological findings. Results: 10 subjects (9 male, mean age 68 years) with biopsy-proven MPM (9 epithelioid tumours, 1 biphasic) were included. One subject underwent neo-adjuvant chemotherapy between imaging and surgery and was excluded from the clinical versus pathological stage analysis. Pathological staging was concordant with staging by 18 F-FDG PET/MRI in 67% (n = 6) of subjects, and with 18 F-FDG PET/CT staging in 33% (n = 3). Pathological T stage was concordant with 18 F-FDG PET/MRI in 78% (n = 7), and with 18 F-FDG PET/CT in 33% (n = 3) of subjects. Pathological N stage was concordant with both 18 F-FDG PET/MRI and 18 F-FDG PET/CT in 78% (n = 7) of cases. No subject had metastatic disease. There was good inter-observer agreement for overall PET/MRI staging (weighted kappa 0.63) with moderate inter-reader agreement for T staging (weighted kappa 0.59). All 6 subjects with prior talc pleurodesis demonstrated mismatch between elevated FDG uptake and restricted diffusion in areas of visible talc deposition. Conclusion: Clinical MPM staging by 18 F-FDG PET/MRI is feasible, and potentially provides more accurate loco-regional staging than PET/CT, particularly in T staging.